Sistem Pemantauan Ruangan Laboratorium Dengan Raspberry Pi Camera - Donalson Libertin (Electrices, 2020)
In the Electrical Engineering Laboratory 2nd Floor room, there is a variety of equipment, but the equipment is often lost. So the room needed a monitoring system to see the activity in the room to minimize theft. The purpose of this study is to design a monitoring system using Raspberry Pi Zero W as a link between the Raspberry Pi Camera and the admin. Room conditions can be monitored online and in realtime on the Web. Based on the results of testing video streaming displayed on the Web, there is a delay of 3-4 seconds so that the image moves slower than the actual situation. This device can send a notification of the condition of the room and pictures at 12: 00-13: 00 when there is movement or someone doing activities in the room. Data is sent via email and google drive @sctolipnj.